1990
DOI: 10.1182/blood.v76.9.1739.bloodjournal7691739
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of plasma cells in normal human bone marrow by high-resolution flow cytometry

Abstract: The low frequency of plasma cells and the lack of specific cell surface markers has been a major obstacle for a detailed characterization of plasma cells in normal human bone marrow. Multiparameter flow cytometry enabled the identification of plasma cells in normal bone marrow aspirates. The plasma cells were located in a unique position in the correlation of forward light scattering, orthogonal light scattering, and immunofluorescent-labeled CD38. The identity of the sorted cell populations was confirmed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Different from blood PB/PC, CD19 is clearly differentially expressed among mature BM and mucosal lamina propria, and CD19 − PC shown consistent features of PC that have reached an exceptionally mature state [ 901 , 1078 , 1116 ]. The frequency of PC in BM cell suspensions is usually greater than in the blood, amounting to 0.5-2% in mononuclear cells after density gradient enrichment, or, to <0.5% of nucleated cells in total BM aspirates [ 1117 , 1118 ]. Donor age may influence the abundance of blood PB/PC and BM PC [ 1106 , 1119 ].…”
Section: B Cell Phenotypesmentioning
confidence: 99%
“…Different from blood PB/PC, CD19 is clearly differentially expressed among mature BM and mucosal lamina propria, and CD19 − PC shown consistent features of PC that have reached an exceptionally mature state [ 901 , 1078 , 1116 ]. The frequency of PC in BM cell suspensions is usually greater than in the blood, amounting to 0.5-2% in mononuclear cells after density gradient enrichment, or, to <0.5% of nucleated cells in total BM aspirates [ 1117 , 1118 ]. Donor age may influence the abundance of blood PB/PC and BM PC [ 1106 , 1119 ].…”
Section: B Cell Phenotypesmentioning
confidence: 99%
“…With each infection or vaccination, despite the addition of 10,000-100,000 newly-minted ASC 12,16 , only a small fraction undergoes maturation into LLPC 13 . Of the total BM nucleated cells, the ASC pool represents a tiny fraction (0.1%-0.3%) over a lifetime 41 . Thus, FACS sorting rare ASC populations with total purity has rendered technical limitations for bulk proliferation studies due to contaminating B cells that may undergoing proliferation.…”
Section: Challenges Of Assessing Proliferation Status Of Human Asc Pr...mentioning
confidence: 99%
“…Examining the genomic profile in NHP cell products is crucial for understanding how likely experiments using these cells are going to mimic a human cell product. Using flow cytometry, Terstappen et al showed that the canonical human PC marker, CD38 is expressed by NHP bone marrow-derived PCs 10 . Furthermore, single-cell RNA sequencing was used to demonstrate that NHP PCs from blood, bone marrow, and lymph nodes express similar factors as human primary PCs.…”
Section: Introductionmentioning
confidence: 99%